Comparison of nebulization with lignocaine and dexamethasone for attenuation of post-operative sore throat: A randomized controlled trial - Rahul Saini; Sanjay Johar; Rahul Deora; Pritam Yadav; Preeti Gehlaut; Prashant Kumar (Asian Journal of Medical Sciences, 2024)
Background: Post-operative sore throat (POST) is a very common anesthesia-related event which may hamper patient satisfaction and increase treatment cost. Aims and Objectives: This study aimed to compare the effectiveness of nebulization with dexamethasone and lignocaine to prevent POST. Materials and Methods: This randomized controlled study involved 135 patients randomly divided into three equal groups: Group D – (n=45) received 8 mg (2 mL) dexamethasone plus 3 mL of distilled water, Group L – (n=45) received 80 mg (4% lignocaine 2 mL) plus 3 mL distilled, and Group S – (n=45) received nebulization with 5 mL normal saline. Results: At 4 h postoperatively, the incidence of POST was 15.6% in the dexamethasone group, 33.3% in the lignocaine group, and 73.3% in the saline group. The score was significantly higher in the saline group (P=0.001) compared to the dexamethasone and lignocaine group, while it was comparable between dexamethasone and lignocaine group (P=0.188). Similarly, dexamethasone and lignocaine groups were comparable at immediately post-operative, 2, 8, 12, and 24 h post-operative time points. Post-operative hoarseness scores of all three groups were comparable at all-time points. A significant increase in the heart rate (HR) and mean arterial pressure (MAP) after intubation was observed in the saline and dexamethasone group as compared to the lignocaine group (P=0.001) while HR and MAP were comparable in dexamethasone and saline group (P=1.000). Conclusion: Dexamethasone and lignocaine nebulization are both effective and comparable prophylaxis for POST and lignocaine nebulization has added advantage of blunting pressor response to endotracheal intubation over dexamethasone nebulization.